2018
DOI: 10.1111/gcb.14503
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between carbon stocks and biodiversity in European temperate forests

Abstract: Policies to mitigate climate change and biodiversity loss often assume that protecting carbon‐rich forests provides co‐benefits in terms of biodiversity, due to the spatial congruence of carbon stocks and biodiversity at biogeographic scales. However, it remains unclear whether this holds at the scales relevant for management, and particularly large knowledge gaps exist for temperate forests and for taxa other than trees. We built a comprehensive dataset of Central European temperate forest structure and multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 66 publications
3
51
0
Order By: Relevance
“…Obviously, given the high average growing stock in the forests, harvesting improves light conditions near the ground and thus facilitates regeneration and establishment of more light demanding species (Boch et al 2013). This finding is in agreement with those of a recent study that showed that there is no positive effect of aboveground carbon stocks of European broadleaved forests on multi-taxa biodiversity (Sabatini et al 2019). This study showed that in particular among plant species, more species are lost than gained with increasing aboveground carbon stocks; including those shade-intolerant and drought-tolerant species which may be required for adaptation of forests to climate change (Kunz et al 2018).…”
Section: Influence Of Harvests On Individual Structural Variablessupporting
confidence: 91%
See 1 more Smart Citation
“…Obviously, given the high average growing stock in the forests, harvesting improves light conditions near the ground and thus facilitates regeneration and establishment of more light demanding species (Boch et al 2013). This finding is in agreement with those of a recent study that showed that there is no positive effect of aboveground carbon stocks of European broadleaved forests on multi-taxa biodiversity (Sabatini et al 2019). This study showed that in particular among plant species, more species are lost than gained with increasing aboveground carbon stocks; including those shade-intolerant and drought-tolerant species which may be required for adaptation of forests to climate change (Kunz et al 2018).…”
Section: Influence Of Harvests On Individual Structural Variablessupporting
confidence: 91%
“…Therefore, influences of harvests or harvesting intensity can have totally different impacts on single taxonomic groups or individual species within taxonomic groups. As has been shown by Sabatini et al (2019) within the taxonomic groups of vascular plants, lichens, fungi, bryophytes, beetles, and birds found in oak and beech dominated forests, the majority of species are not influenced by aboveground biomass C stocks, yet within each of these groups there are some winners and losers of increasing or decreasing stocks.…”
Section: Influence Of Harvests On Individual Structural Variablesmentioning
confidence: 85%
“…habitat of threatened species), as well as other ecosystem services (e.g. timber provisioning) would be a useful follow‐up undertaking for some biomes (Mönkkönen et al., 2014; Sabatini et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…), but also weak relationships at the stand scale (Sabatini et al. ). We show that preserving forests in the western United States with high productivity and low vulnerability to future fire and drought can aid in the maintenance of vertebrate biodiversity, as these forests contain the highest proportion of critical habitat for threatened and endangered species.…”
Section: Discussionmentioning
confidence: 99%